Aplikasi Realiti Pergerakan (AR) Untuk Standard Subjek Sains Tahun 5 Sekolah Rendah, (AR Jirim) - Azrie, Ahmad Fakhrul Hadi; Rosdi, Ahmad Naim Hakimi; Muhamad Idris Hafit; Ibrahim, Zuraida (Multidisciplinary Applied Research and Innovation, 2022)
Augmented Reality (AR) Application targeted for Primary School for Year 5 Science Subject Standard Matter topic is a Smart Application built using visual object method via computer for use of Matter topic science subject found in primary school syllabus. It is found that the problem faced by students in school is the way of learning that uses traditional methods such as taking notes or books as a basic guide in their learning sessions which are found to be less attractive to students to understand this subject. This study was conducted to attract students’ interest in science subjects, especially the topic of Matter which was found to be less interesting to them. In addition, this application is also developed to give students a clear picture of the topic of Matter through the latest technology that is Augmented Reality (AR) Technology and provide an advantage in the education sector. Therefore, the methodology to be used in the development of this project is the WATERFALL model. This model was chosen because it is the most suitable and most relevant method to be applied in the development of this smart application as well as the number of phases found in this method can help provide a structured guide during the process of developing the application. The phases are analysis, design, development, implementation and evaluation. Therefore, it is hoped that this project will be able to provide benefits and broad exposure to all strata of society on the benefits of this technology, especially those involved in the Education sector, namely schools, teachers and students to learn and teach science subjects more efficiently. through the application of Movement Reality or AR technology